2021
DOI: 10.1002/met.2024
|View full text |Cite
|
Sign up to set email alerts
|

Responses of extreme high temperatures to urbanization in the Beijing–Tianjin–Hebei urban agglomeration in the context of a changing climate

Abstract: Extreme high-temperature event is one of the most urgent climate issues faced by coordinated development of the Beijing-Tianjin-Hebei region (BTH) in the future due to global warming and urbanization. Based on the homogenized daily temperatures from 174 meteorological observation stations, six extreme hot events were detected. The results revealed the spatiotemporal change characteristics of the extreme high temperature in the BTH. The acquired evidence showed the maximum daily minimum temperature (TNx), high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…It may be associated with the larger proportion of impervious surface area and the enhanced WPSH (Chen et al., 2020). A relatively small increase in the BTH is possibly due to the cooling caused by intense haze pollution and expanding irrigation (Wang, Chen, et al., 2021; Wang, Ren, et al., 2021; Wu et al., 2018). As to the intensity of CHEs, it was the strongest with the most significant increase in the YRD, followed by the PRD and the BTH.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It may be associated with the larger proportion of impervious surface area and the enhanced WPSH (Chen et al., 2020). A relatively small increase in the BTH is possibly due to the cooling caused by intense haze pollution and expanding irrigation (Wang, Chen, et al., 2021; Wang, Ren, et al., 2021; Wu et al., 2018). As to the intensity of CHEs, it was the strongest with the most significant increase in the YRD, followed by the PRD and the BTH.…”
Section: Resultsmentioning
confidence: 99%
“…Trenberth and Fasullo (2012) pointed out that the CHE in 2010 led to widespread wildfires in Russian, inducing devastating losses of human life and economy. It is projected that the frequency of CHEs will increase by two to five times in the 2090s compared to the 2010s in China (Wang, Chen, et al., 2021; Wang, Ren, et al., 2021). By the mid‐21st century, 50% of land area of the BTH, YRD, and PRD will experience CHEs unprecedented in history (Wang et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors highlight that past land cover changes (from 1878 to 2012) had a significant effect on urban temperatures, while weaker variations are estimated for the future since the growth of the urban area is expected to be less significant. On the other hand, the effects of ongoing climate change on urban conditions are evaluated by Wang et al (2021), who analyse data from 174 meteorological stations in the Beijing‐Tianjin‐Hebei region (China) to evaluate trends in six ETCCDI indices. The authors highlight increasing trends for most of the indices, also showing the significant contribution of urbanisation.…”
Section: Urban Areas Heat Stress and Air Pollutionmentioning
confidence: 99%
“…In the process of socioeconomic development, different regions have a variety of land use needs as well as unique land use structure characteristics [71,72]. Wang et al argued that regional planning policies can influence the degree of urbanization [73], whereas Gong et al reported that while the implementation of land use policies is beneficial to ecosystem functioning, it may also exacerbate water scarcity [74]. Therefore, it is necessary to link socio-economic with sustainable development, and to optimize and adjust the regional land structure and rationalize the use of regional land resources.…”
Section: Future Land Structure Optimizationmentioning
confidence: 99%